Pengaruh Disiplin Kerja Terhadap Kinerja Aparatur Sipil Negara Bagian Protokol dan Komunikasi Pimpinan Kabupaten Badung - Gde Adinatha Gama (Universitas Warmadewa, 2023)
Work discipline relates to how an individual implements the rules and norms that apply in the work environment related to the responsibilities that have been given as a form of encouragement for an agency to achieve what is the vision and mission of the agency concerned. The purpose of this research is to analyze how work discipline relates to the performance of the state civil apparatus and to find out how work discipline influences the performance of the state civil apparatus. The approach used in this study uses a qualitative approach which depicts the results of the observations made by the researcher. Data collection was carried out by observation, interviews, and documentation which were then analyzed descriptively with their validity assessed using a triangulation technique. The results of the study show that work discipline greatly influences the performance of state civil servants in the Protocol and Leadership Communications Section. This is related to efforts to achieve what has been expected and aspired to in an institution. In addition, employees are also very aware of how important it is to carry out a work discipline, this is related to the responsibilities of employees in completing their work by implementing the rules and norms that apply in the workplace.